Reading the Body in Dickens’s Bleak House and Our Mutual Friend - Harputlu Shah, Zeynep (Complutense Journal of English Studies, 2019)
This article examines the ways in which the Victorian body and identity were being transformed in the mid-nineteenth century and identifies three distinctive ways the biological and normative boundaries of the body were violated as represented in Dickens’s fiction: the grotesque body, the vulnerable body and the dead body. In this sense, Dickens’s Bleak House (1851-53) and Our Mutual Friend (1864-65) present creative and challenging literary responses to the Victorian body abjected through deprivation, physical vulnerability and death. In the novels, the grotesque body challenges the abject via a tragicomic and hybrid representation of the body and of character. Regarding the vulnerable body, the study elaborates on a body “out-of-control”, threatening the boundaries between the object and the subject, inside and outside, by holding a liminal state through ill-health, excessive labour, starvation and physical degradation. Finally, it is argued that there was an intimate and abject relationship between the living and the dead bodies in the capital, beside prevalent infant deaths, high mortality rates, diseased bodies and overflowing graveyards in the city.